Neural Action of Androgens in the Suprachiasmatic Nucleus Brain Clock - Coome, Lindsay (2013)
The suprachiasmatic nucleus (SCN) of the hypothalamus is the locus of a master circadian clock that is critical in the temporal organization of circadian activity. The SCN coordinates the rhythmic secretion of gonadal hormones, and in turn, reproductive hormones may act on their receptors within the SCN to alter circadian function. Using transgenic mice that over-express androgen receptor (AR) only in neurons, the current study investigated the influence of neural AR on the function of the SCN. In particular, it addressed the effects of androgens on circadian behaviours as well as physiological responses to light within the SCN by measuring Fos response after a phase-shifting light pulse. It was found that transgenic mice demonstrate a smaller increase in Fos expression in response to a light pulse than do wildtypes. Interpretations of our findings, including the possible functional significance of AR within the SCN, are discussed.